(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
Road safety has always been under special attention of the government of Uzbekistan. Since 1991, when Uzbekistan became independent, more than 100 laws and regulations have been adopted related to road safety, traffic rules, training and education, vehicle inspection, insurance, etc. It is recognized that there are common legal frameworks, road design standards, vehicle design specifications and road safety management frameworks. As in many countries, the question arises whether these documents correspond to modern standards and how these laws are implemented in practice.